Children’s rights and their evidence as a force for inclusion in uncertain times - Bourke, Roseanna (Frontiers in Education, 2023)
Although education is a basic child’s right, and in many countries is protected through legislation, children with disabilities or support needs are not always afforded their right to experience an education at their local school alongside their peers. There is even less evidence that their ‘voices’ are sought or heard when decisions are made for them. This silencing of children in education results in their views being invisible in practice. When making decisions about children’s education and opportunities, an evidence-based model could feasibly address this, if the child’s right to have a say was afforded the same weighting as that of the input from practitioners, and research findings. Evidence-based practice in education typically relies on three forms of evidence: (i) systematic research that has been published or disseminated, (ii) specific practitioner knowledge and experience of children and their needs, and (iii) the children’s and their family’s experience of their own lived lives and capabilities. Combined, these forms of evidence can illuminate the decisions made for an individual child, and forge the pathway for interventions, actions, and solutions that are most likely to ‘work’ for the child, their culture, and their context, all things considered. However, there remains a tension when weighing up the relative status of these forms of evidence, where ‘research’ or ‘expert opinion’ is given more credence than the child’s capabilities: that is, less weighting is given to an individual child’s expression of their circumstance, their context, their ethnicity, and the opportunities afforded to them. When practitioners’ expertise is given more emphasis in decision-making around inclusion or educational options for the child, than the child’s own aspirations, there will always be a gap in evidence-based practice. Placed against rights-based practice, it becomes even more critical to give every child their ‘voice’, and where possible, to act on their views, as the children are the key informant for their own solutions, and of their own interpretation and expression of the ‘problem’.